Trabalho e formação docente em educação física na educação de jovens e adultos na rede municipal de Belém/PA - COSTA, Maria da Conceição dos Santos (Universidade Federal do Pará, 2017)
This study analyzes the configuration of work and training of teachers of Physical Education performing in “Education of Youth and Adults Program”- EJA, in the Municipal Education Network of Belém-PA, from the context of productive restructuring it also stresses that these fields have been subsumed to the capital agenda, suffering determinations that directly interfere with the working-life class. In the study, Physical Education is understood as a pedagogical field that deals with the knowledge produced historically by humanity in the field of Corporal Culture, and the “Education of Youth and Adults” is considered as a field of resistence of the working class that historically has been excluded from access and permanence to the Public School of quality, socially referenced. It has been developed based on theoretical and methodological support from a critical perspective, through a literature and document review and a field research, conducting interviews and questionnaires applied to Physical Education teachers who work in the “Education of Youth and Adults Program” in the municipal education system of Belém, and took as an analytical reference the methodological elements of content analysis. As a result, the study revealed that the teaching work has taken place in an expropriated, precarious, intensified and solitary way and that the training conditions have been materialized in a precarious way, not occurring integrally in the initial training courses to work with young people and adults, but based on life experiences and experiences that materialize from the teaching work in the public school. The social, cultural and economic diversity of young people and adults and the context of violence that marks the present society represent great challenges to the teaching work in this modality of education. The process experienced by Physical Education teachers, in their work and training, and the precariousness in the school context, with the closure of EJA classes in the municipal education system, aggravate the process of exclusion of young and adult workers and causes the resistence of teachers, who construct educational possibilities in PE with young and adults workers, seeking alternatives based on their own experiences, exchanges with other teachers, and dialogues in the public school.